Effects of terrain slope on water distribution and application uniformity for sprinkler irrigation - Zhang, Lin; Hui, Xin; Chen, Junying (International Journal of Agricultural and Biological Engineering, 2018)
In order to provide practical parameters for sprinkler irrigation system design on slope land, the effects of terrain slope on water distribution, sprinkler throw radius and water application uniformity were analyzed for the Rainbird LF1200 sprinkler. The results show that, the water distribution curve is roughly “heart-shape” on slope land, and the water has the trend of focusing on the upslope with the increase of the slope. Throw radius decreases for the upslope and increases for the downslope as the slope increases. For the convenience of sprinkler irrigation system design on slope land, a formula for computing throw radius on slope land was put forward by the theoretical derivation, and it was verified by the experimental data. The impact of sprinkler pressure and spacing on CU for slope land is more significant than that for flat ground. Under the experimental condition, no significant change is found regarding the influence of terrain slope on water application uniformity at the confidence level of 95%. Taking irrigation quality and economy into account, the Rainbird LF1200 sprinkler should be operated at the manufactures’ recommended pressure, rather than low pressure, with sprinkler spacing from 8 m×8 m to 10 m×10 m below the slope of 0.15 in practice. Keywords: sprinkler irrigation, slope land, water distribution, water application uniformity, throw radius DOI: 10.25165/j.ijabe.20181103.2901 Citation: Zhang L, Hui X, Chen J Y. Effects of terrain slope on water distribution and application uniformity for sprinkler irrigation. Int J Agric & Biol Eng, 2018; 11(3): 120–125.